PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN PUBLIK DI INDONESIA (Studi Empiris Pada Perusahaan Manufaktur di BEI 2012-2014) - Wijayani, Dianing Ratna (Universitas Airlangga, 2017)
The purpose of this research was to examine the effect of intellectual capital on Return On Assets, Earning Per Share and Return On Equity. The population of this research is manufacturing companies listed on the Stock Exchange the period 2012-2014, a total sample of companies amounted to 51 samples were taken by using purposive sampling method. The method of analysis in this research is multiplelinear regression analysis. The results of this study indicate that intellectual capitalsignificant positive effect on ROA. This condition occurs because if the human resource capacity the better, it is expected to produce profitability Return on Assetsincreased. Intellectual capital is significant positive effect on EPS. This condition occurs because when intellectual capital is getting better, the public trust in the company, the better, so that the products or services offered by the company is accepted by the community and increasing revenue. Intellectual capital is significant positive effect on ROE. This condition occurs because the intellectual capital increases, the company has been using its capital more effectively to improve human resources, so that the performance of employees to generate increasing profits.